2017
DOI: 10.3389/fmicb.2017.00753
|View full text |Cite
|
Sign up to set email alerts
|

Non-edible Oil Cakes as a Novel Substrate for DPA Production and Augmenting Biocontrol Activity of Paecilomyces variotii

Abstract: The present study investigated the use of waste non-edible oil cakes (Jatropha, Karanja, Neem, and Mahua) as a substrate for the growth of Paecilomyces variotii and dipicolinic acid (DPA) production. Previous researches proved the efficacy of DPA in suppressing certain pathogens that are deleterious to the plants in the rhizosphere. DPA production was statistical optimized by amending non-edible oil cakes in growing media as nitrogen and sugars (Dextrose, Glucose, and Lactose) as carbon source. Plackett-Burman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1d) a modular design patented by Biocon Ltd. claimed for a self-contained SSF device that combined all fermentation operations i.e., sterilization, inoculation, cultivation, extraction and post-extraction treatment, in a single unit. It was validated for sterile production of proteases, cyclosporine, amylases and lovastatin [15,32,34].…”
Section: Static Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1d) a modular design patented by Biocon Ltd. claimed for a self-contained SSF device that combined all fermentation operations i.e., sterilization, inoculation, cultivation, extraction and post-extraction treatment, in a single unit. It was validated for sterile production of proteases, cyclosporine, amylases and lovastatin [15,32,34].…”
Section: Static Bioreactorsmentioning
confidence: 99%
“…This non-sterile bioreactor is equipped with controls for process parameters (air-inlet temperature, air flow rate and agitation period). Different working volumes are available, but a maximum layer thickness of [15,32,34] 50 cm is used. Substrate is prepared and inoculated in other equipment before filling the reactor [14,15,32].…”
Section: Agitated Bioreactorsmentioning
confidence: 99%
“…In in vitro test, nanshancha seed cake (Camellia semiserrata Chi) showed percentage inhibition of 100, 90.9, 85.3% against Colletotrichum musae, C. gloeosporioides, and Penicillium italicum, respectively [36]. Few researchers have reported the antagonistic effect of oilseed cakes against fungal phytopathogens that support the biocontrol efficacy of oilseed cake in the present study [9,36]. Furthermore, in the present study, solid-state fermentation of F. oxysporum on mustard cake showed an inhibitory effect on spore production.…”
Section: Discussionmentioning
confidence: 46%
“…Tiyagi [10] reported that damage caused by nematodes in Vigna radiata was less pronounced after a combined application of oilseed cake and Pseudomonas fluorescens. Arora [9] assessed the efficiency of oil cake as a novel growth substrate for Paecilomyces variotii that augmented its antagonistic activity against F. oxysporum and Verticillium dahliae. These earlier studies provided an approach for the present work to utilize mustard cake in combination with biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation